Various workload models and the preseason are associated with injuries in professional female cyclists - van Erp, T.; van der Hoorn, T.; Hoozemans, M. J. M.; Foster, C.; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To determine if workload and seasonal periods (preseason vs in season) are associated with the incidence of injuries and illnesses in female professional cyclists.